Taxonomic revision of the genus Eudonia Billberg, 1820 from China (Lepidoptera: Crambidae: Scopariinae) - Li, Weichun; Li, Houhun; Nuss, Matthias (Zootaxa, 2012)
The Chinese species of the genus Eudonia Billberg, 1820 are revised, and in total 25 species are recognized including 10new to science as follows: E. singulannulata sp. n., E. rectilineata sp. n., E. wolongensis sp. n., E. zhongdianensis sp. n.,E. lijiangensis sp. n., E. hexamera sp. n., E. furva sp. n., E. magna sp. n., E. duospinata sp. n. and E. cavata sp. n. Eudoniapersimilis Sasaki, 1991 and E. puellaris Sasaki, 1991 are recorded for the first time from China. Eudonia altissima Leraut,1986, syn. n. is synonymised with E. tibetalis (Caradja, 1937). Images of the adults and genitalia of the new species areprovided, along with keys for the identification of the Chinese species based on both male and female genitalia. A distribution map of Eudonia in China is included.